ANAGEMENT OF PROXIMAL HUMERUS FRACTURE IN ADULTS WITH PHILOS PLATE FIXATION IN NEER TYPE 2 AND TYPE 3 - Kakati, Ankur; Garg, Shivam; Rathi, Rahul; Meena, Laxmi Narayan; Maharia, Ravikant (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: One of the most frequent bone fractures is a fracture of the proximal humerus. They make up between 4% and 5% of all fracture. With less invasive soft-tissue injury and a lower risk of iatrogenic avascular necrosis, closed reduction and percutaneous fixation have become more popular in recent years as opposed to open reduction (OR) and extensive internal fixation (IF) (by plates and screws). The aim of this study was to compare the functional results of proximal humerous locking osteosynthesis (PHILOS) fixation against OR and IF of proximal humerus fractures (2 and 3 Neer’s classification). Methodology: This study involved 40 patients, with a mean age of 53 and a range of ages from 18 to 55, with 2 and 3 part fractures according to Neer’s classification. Patients were randomized to either group, with Group I type 2 fractures receiving OR and IF for 22 patients, and Group II (type 3 fractures) with 18 patients receiving PHILOS plate fixation, with function assessed using the CMS score. Results: At 1 month, 3 months, and 6 months of follow-up, Group I’s mean Visual analog scale (VAS) score decreased to 2.52, 2.10, and 1.22 and in Group II, 3.86, 2.64, and 2.41. The VAS score was reduced and function CMS score were significantly increased in Group I (80% VAS score, 65% CMS score) as compared to Group II (64% VAS score, and 58%CMS score). At 1, 3, and 6 months, there was a statistically significant difference between the two groups. Conclusion: Both groups saw satisfactory results, with each method having benefits and drawbacks. We discovered that plate fixation provided stable fixation with few implant problems and early range-of-motion exercise to achieve acceptable functional results.